Mutualistic Partnership Of Msme’s Culinary Center With Uptd Mangrove Botanical Gardens Of Surabaya City - Fadhilah, Risca Nur; Nafi'ah, Binti Azizatun (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The city of Surabaya is currently intensively developing its tourism potential. One of the tourist destinations that is being created is the Surabaya City Mangrove Botanical Garden. In the development process, the government provides space for establishing partnerships with street vendors who previously sold there to fill the vacancies in the culinary center stands in the Mangrove Botanical Gardens. This research aims to analyze the partnership between the MSME Culinary Center and the UPTD Mangrove Botanical Gardens in Surabaya City so that it can provide benefits to increase competitiveness and sustainably strengthen ecotourism. However, there are still several complaints from MSME culinary center players. The research method used is descriptive through observation, interviews, and documentation. Data sources are obtained from primary data and secondary data. The focus of this research uses the theory of the mutualistic partnership model (Sulitiyani, 2017) because both are aware of the sense of providing mutual benefits and getting benefits based on the analysis of three principles of partnership, namely equality, transparency, and mutual win-win solution. The results obtained from this research are as follows: 1) In its implementation, equality has not gone well because there is no cooperation agreement/MoU in the aspect of mutual trust. However, the MSME Culinary Center and UPTD Mangrove Botanical Gardens have an agreement approved by the MSME actors, and there is a lack of respect for the rules for visitors. 2) in its implementation, transparency has been carried out well because both have the ease of clear communication, transparency of information on management and ordering food and large minimums and transparency of information about financial management. 3) Win-win solution: The implementation is quite good because MSME Culinary Center Operators benefit from additional turnover from sales proceeds and facilities provided by the UPTD Managing the Mangrove Botanical Gardens, while the UPTD Managing the Mangrove Botanical Gardens gets an increase in Regional Original Income (PAD) from ticketing, even though the promotion aspect of the Medokan Sawah culinary center is not yet optimal.